Market Leader. International Management - Pilbeam A. Adrian (Business English)
Market Leader is an extensive new Business English course which brings the real world of international business into the classroom. Developed in association with the Financial Times, it offers the widest and most flexible range of materials for learners and teachers alike. Key features of Market Leader: • Authentic texts from the Financial Times and other sources • Up-to-date business topics and issues • Comprehensive language and skills practice • Highly motivating case studies • A dedicated website with a regular supply of new texts and work sheets to download at www.market-leader.net <http://www.market-leader.net>International Management is one of a number of specialist books within the Market Leader series. These books concentrate on reading skills and vocabulary development for students specialising in particular aspects of business. Other titles in the series include Business Law and Banking and Finance. Each book consists of 18 units, 2 tests and a multilingual glossary.